Research fundamental deformation features of composite materials with low connectivity in conditions of plane strain. - Багрій, О.В. (Problems of Tribology, 2016)
The character of the deformation of solid materials with low molecular connection is investigated. It is shown that the surface can be represented as the sum of the Coulomb friction surface and the surface of the Prandtl ideally cohesive material. This allows independent study of the influence of molecular connectivity and internal Coulomb friction on the deformations of solids, and the value of the variable modules of deformation to determine directly from the total surface deformation or as a sum of modules, found on the surface of the Prandtl and the surface of the Coulomb.Keywords: composite material, сoulomb's surface, рrandtl surface, strain, deformation, variable shear modulus.